Open API untuk Warung Makan Usaha Kecil dan Industri Rumahan - Tekad Matulatan; Nerfita Nikentari; Martaleli Bettiza; Hendra Kurniawan; Nola Ritha (Jurnal Teknologi dan Riset Terapan (JATRA), 2020)
Many food stalls are small businesses or home industries with a capital under 10 million rupiah and are generally located in the yard of the stall owner, and do not have branches. The most common obstacle was the lack of customers caused by the location of the stall which was not strategic and the information about the stall service was not widespread. OPEN API Warung Makan is the implementation of Community Service activities funded from an internal grant 2019 Raja Ali Haji Maritime University. This API is intended to be open to any application developer to take advantage of this free service to be aimed at food stalls that fall into the category of small businesses or home industries. OPEN API Warung Makan provides two parts of service, namely for customers and stall owners. OPEN API Warung Makan uses Raja Ali Haji Maritime University's cloud infrastructure and does not require Authentication Tokens or the like.